Teachers' learning : stories of science education - Wallace, John (John William), 1947- (Science & technology education library ;, 2000)
"Teachers' Learning: Stories of Science Education is aimed at science educators who wish for a deeper understanding of how teachers learn to teach science and the role of stories in reporting science education research. It is fascinating look at the knowledge teachers have and use, how context influences teachers' work, and the role of reflection and collaboration in teachers' learning."--Jacket